A holistic approach to marketing growth of small and medium enterprises: development and application of the HMGI index - Heorhitsa, Vladyslav (Management and Entrepreneurship: Trends of Development, 2025)
The article explores a holistic approach to assessing marketing growth in small and medium-sized enterprises (SMEs). This approach is intended to replace fragmented metrics that capture only isolated aspects and often focus on short-term outcomes. The purpose of the study is to propose the Holistic Marketing Growth Index (HMGI) as an easy-to-use yet comprehensive tool that demonstrates how marketing contributes to overall company growth. The subject of the research is the systemic evaluation of marketing performance across several groups of indicators: financial results, brand strength, customer behavior, effectiveness of digital channels, and the company’s internal capacity for renewal and development.The HMGI method consists of several steps. First, the relevant indicators are selected. Next, they are normalized to a common scale to ensure comparability. Each group of indicators is then assigned a weight, and all results are combined into a single index. The method also provides for comparison with typical industry benchmarks and tracking of dynamics over time. This procedure makes the data easier to interpret and allows managers to identify what is working well and what requires attention quickly. An illustrative example demonstrates that an integrated view more accurately reflects the real contribution of marketing to business growth than analyzing individual KPIs. In addition, the index helps to detect interactions between channels and direct investments to areas with the highest potential impact.The findings indicate that HMGI can serve as a practical tool for business owners and executives: it helps with planning, setting priorities, and clearly communicating decisions to teams and partners. The scientific novelty lies in bringing diverse indicators into a single, coherent system that can be updated and used for continuous monitoring. The practical value is reflected in the rapid diagnosis of strengths and weaknesses of a marketing strategy and the support of accurate, evidence-based decisions. Limitations include the quality of input data and the choice of weights. Future research should focus on testing the model across different markets, validating it with real companies, and expanding the set of indicators.JEL Classification: М31, О32, L26